Hemorrhagic Shock: Blood Marker Sequencing and Pulmonary Gas Exchange - Benedikt Treml; Axel Kleinsasser; Johann Knotzer; Robert Breitkopf; Corinna Velik-Salchner; Sasa Rajsic (Diagnostics, 2023)
Background: The early identification of internal hemorrhage in critically ill patients may be difficult. Besides circulatory parameters, hemoglobin and lactate concentration, metabolic acidosis and hyperglycemia serve as laboratory markers for bleeding. In this experiment, we examined pulmonary gas exchange in a porcine model of hemorrhagic shock. Moreover, we sought to investigate if a chronological order of appearance regarding hemoglobin, lactatemia, standard base excess/deficit (SBED) and hyperglycemia exists in early severe hemorrhage. Methods: In this prospective, laboratory study, twelve anesthetized pigs were randomly allocated to exsanguination or a control group. Animals in the exsanguination group (n = 6) endured a 65% blood loss over 20 min. No intravenous fluids were administered. Measurements were taken before, immediately after, and at 60 min after the completed exsanguination. Measurements included pulmonary and systemic hemodynamic variables, hemoglobin concentration, lactate, base excess (SBED), glucose concentration, arterial blood gases, and a multiple inert gas assessment of pulmonary function. Results: At baseline, variables were comparable. Immediately after exsanguination, lactate and blood glucose were increased (p = 0.001). The arterial partial pressure of oxygen was increased at 60 min after exsanguination (p = 0.04) owing to a decrease in intrapulmonary right-to-left shunt and less ventilation-perfusion inequality. SBED was different to the control only at 60 min post bleeding (p < 0.001). Hemoglobin concentration did not change at any time (p = 0.97 and p = 0.14). Conclusions: In experimental shock, markers of blood loss became positive in chronological order: lactate and blood glucose concentrations were raised immediately after blood loss, while changes in SBED lagged behind and became significant one hour later. Pulmonary gas exchange is improved in shock.